Real time control of buck converter with Sugeno Fuzzy Inference System using Arduino - Iskandar, Adrian; Yuhendri, Muldi (Department of Electrical Engineering Universitas Negeri Padang, 2024)
As time progresses, technology for electrical and electronic equipment also develops very rapidly, generally these electronic devices use electrical energy as a source, energy sources also vary from high voltage for industry and low voltage for household appliances. There are two types of voltage, namely direct and alternating. This direct voltage can be obtained from a DC generator, battery, or AC voltage that is directed to DC. In general, a buck converter has the meaning of reducing DC to DC voltage which has two types of storage, namely capacitor and inductor, thus producing a small ripple value. To be able to get the appropriate voltage value, the output value needs to be set via the Simulink Matlab program, namely Sugeno Fuzzy Inference System. Buck converters that have been set using different settings are different from those that have not been set using fuzzy. Buck converter circuits that do not use a control system only reduce the voltage according to the existing results and if you want to change the output results then we have to change the duty cycle value manually of course this will not be effective in the long term or using the tool periodically whereas if you use a fuzzy control system We can set the output value of the buck converter according to what we need